The Relationship between Parents' Religiosity Level and Islamic Religious Education Learning Achievement - Pratama, Surya Adi; Pramana, Ardi (Episteme: Jurnal Kajian Mahasiswa, 2025)
This study investigates the relationship between parental religiosity and students’ academic achievement in Islamic Religious Education (IRE) at SDN 1 Sukanegara. The research addresses the issue that, despite growing interest in Islamic-based education, the influence of parents’ religious commitment on student outcomes remains underexplored. The purpose is to assess the level of parental religiosity, evaluate student achievement in IRE, and analyze their correlation. Using a quantitative approach with correlation analysis, data were collected through questionnaires and school records. Results indicate a significant positive relationship between parents' religiosity and student performance in IRE. The findings suggest that parental religious involvement contributes to students' moral development and academic success. This research highlights the importance of family-based religious support in enhancing formal Islamic education.